The use of an interleukin 1 inhibitor in a patient with atypical course of periodic fever - M. S. Eliseev; O. V. Zhelyabina; A. M. Novikova; M. N. Chikina; M. K. Kurbanmagomedov; M. M. Urumova; E. V. Nikolaeva; S. O. Salugina; E. S. Fedorov; E. L. Nasonov; A. M. Lila (Современная ревматология)
The article presents a case of periodic fever (PF) in a 35-year-old patient, who did not have hereditary and proven genetic factors of the disease, which was characterized by an atypical course with variable in duration and frequency severe abdominal pain and febrile fever attacks, increased acute phase reactants and ineffectiveness of colchicine intake. Differential diagnosis with a wide range of febrile conditions was performed. Daily subcutaneous therapy of interleukin 1 inhibitor (iIL1) at a dose of 100 mg was used as a diagnostic marker to confirm the diagnosis of PF. As a result of the therapy, a rapid (within a few hours after injection) relief of the current attack of the disease, normalization of serum CRP levels, and further complete control over the disease (no relapses) were achieved. Our observation shows that a positive response to iIL1 therapy can serve as a diagnostic marker of PF.